Barriers and Strategies to Engaging Our Community-Based Preceptors. Issue 4 (2nd October 2018) - Graziano, Scott C.; McKenzie, Margaret L.; Abbott, Jodi F.; Buery-Joyner, Samantha D.; Craig, LaTasha B.; Dalrymple, John L.; Forstein, David A.; Hampton, Brittany S.; Page-Ramsey, Sarah M.; Pradhan, Archana; Wolf, Abigail; Hopkins, Laura
ABSTRACT: Issue : This article, from the "To the Point" series that is prepared by the Association of Professors of Gynecology and Obstetrics Undergraduate Medical Education Committee, is a review of commonly cited barriers to recruiting and retaining community-based preceptors in undergraduate medical education and potential strategies to overcome them.Evidence : Community-based preceptors have traditionally served as volunteer, nonsalaried faculty, with academic institutions relying on intrinsic teaching rewards to sustain this model. However, increasing numbers of learners, the burdens of incorporating the electronic medical record in practice, and increasing demands for clinical productivity are making recruitment and retention of community-based preceptors more challenging.Implications : General challenges to engaging preceptors, as well as those unique to women's health, are discussed. Potential solutions are reviewed, including alternative recruitment strategies, faculty development to emphasize efficient teaching practices in the ambulatory setting, offers of online educational resources, and opportunities to incorporate students in value-added roles. Through examples cited in this review, clerkship directors and medical school administrators should have a solid foundation to actively engage their community-based preceptors.